Nonparametric covariate adjustment - Akritas, Michael (Henry Stewart Talks, 2007)
Common parametric and semiparametric approaches for adjusting for covariates, including analysis of variance (ANOVA) and analysis of covariance (ANCOVA), The assumptions underlying their validity, The nonparametric version of the ANOVA model which formulates hypotheses in terms of the cumulative distribution functions as a useful, assumption-free, alternative, Statistics for testing such hypotheses are extensions of the rank-sum statistic to the ANOVA setting and are implemented with the FANOVA and PROC MIXED procedures in SAS, An extension of the nonparametric ANOVA methodology to continuous covariates (ANCOVA), Simulation results, Analysis of data examples: the Penn State Young Women's Health Study (YWHS) and the Etiology of Crime Study
Reviewed at 2017/09/26